Training Teachers for the Career Guidance of High School Students - Otilia Sanda Bersan; Anca Lustrea; Simona Sava; Oana Bobic (MDPI AG, 2024)
The article addresses the decision-making process of career choice among high-school students and emphasizes the importance of supporting their informed decisions by trained teachers acting as career-guidance counselors. While, ideally, school counselors handle career counseling, their limited availability necessitates the involvement of other resources, such as trained teachers. The present study introduces a career-guidance training program for teachers, implemented with 20 Romanian and 20 Serbian teachers. The research conducted simultaneously with the training aimed to assess the effectiveness of this cross-national program in enhancing teachers' competence in career guidance. Utilizing a longitudinal mixed methodology, the study assessed the teachers' perceptions of the training's effectiveness and sustainability over a period of 24 months. Two questionnaires featuring multiple-choice and open-choice questions were employed. The results consistently indicated that teachers rated the training as excellent or very good across various dimensions, including content, trainers, didactic materials, and applications. Challenges were noted in designing and implementing group career activities compared to individual ones, with no significant differences observed between Serbian and Romanian teachers. After 24 months, a deductive content analysis of open-ended questions assessed the sustainability of acquired competencies. Our findings indicated active teacher participation in career-guidance activities, primarily with final-year students serving as class teachers or subject instructors. In the context of a scarcity of career-counseling specialists, training teachers as career-guidance advisors emerges as a viable solution. The study highlights the potential of such training programs to address the critical need for comprehensive career guidance in schools.